Chest Pain in a Patient with Dengue Fever Resembling Acute Myocardial Infarction: A Case Report - Hoque, Sania; Islam Khan, Muhammad Touhidul; Haque, Tausiful (Journal of Armed Forces Medical College, Bangladesh, 2022)
Dengue is an arthropod-borne viral disease. Dengue fever may present with dengue hemorrhagic fever/dengue shock syndrome. Now a days some atypical and rare manifestations are noticed involving liver, central nervous system and heart. Here we reported a case of dengue fever in 25 years young man having high level of cardiac biomarkers and ECG changes mimicking myocardial infarction initially but later on further evaluation of the case confirmed as acute myocarditis due to dengue fever. JAFMC Bangladesh. Vol 17, No 2 (December) 2021: 99-102